Diseño Geométrico de una Rampa de Emergencia con base en la Norma N-PRY-CAR-10-04-007/13 - Hernández Crisóstomo, José Eduardo (My University, 2017)
Norma N-PRY-CAR-10-04-007/13
Keywords: Norma N-PRY-CAR-10-04-007/13